2000
DOI: 10.1097/00004770-200012000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Prophylactic Etodolac on Postendodontic Pain

Abstract: To determine if prophylactic etodolac would significantly reduce postendodontic pain, when compared with ibuprofen or placebo, 36 patients consented to single blind oral administration of either 400 mg of etodolac, 600 mg of ibuprofen, or a placebo, before conventional one-appointment root canal therapy. Patient-reported visual analog scale ratings of pain intensity were conducted upon initial clinical presentation, immediately postoperative, 4, 8, 12, 24, 48, and 72 h after initiation of root canal therapy. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…Menke et al (19) studied patients with varying pulpal and periapical diagnoses. They compared 400 mg etodolac and 600 mg ibuprofen with a placebo in 36 patients postoperatively and at 4, 8, 12, 24, 48, and 72 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menke et al (19) studied patients with varying pulpal and periapical diagnoses. They compared 400 mg etodolac and 600 mg ibuprofen with a placebo in 36 patients postoperatively and at 4, 8, 12, 24, 48, and 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the occurrence of interappointment emergencies (7,8,10,(14)(15)(16), intracanal medicament pain (11,13,21,22), use of analgesics (17)(18)(19)(20)23), and effect of drainage on postoperative pain (4). Unfortunately, many of these studies have not separated the diagnosis of pulpal conditions (vital versus necrotic) and have only evaluated postoperative pain during short time intervals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Continued)20. How many times a day do you recommend your patients take a narcotic pain medication for postoperative pain control?…”
mentioning
confidence: 99%
“…According to our findings, comparing the 2 groups showed a significant effect on reducing the pain at 2, 4, and 8 hours after surgery based on VAS pain score. In a similar study, ibuprofen management significantly reduced pain at 4 and 8 hours after surgery (20). Moreover, Wells et al (2011) compared the use of ibuprofen against ibuprofen/acetaminophen to reduce pain in a randomized double-blind study and found a decrease in pain levels and analgesic use over time for both groups (21,22).…”
Section: Discussionmentioning
confidence: 94%